State Plan Proposals 1989-90 Volume I - Planning Commission (Planning Commission, 1989)
In the Rural sector 1350 villages and 1604 villages were electrified in 1986-87 and 1987-88 respectively. In 1988-89 the state expects to electrify 1850 villages. Number of tube wells energised were 4842 in 189786- and 8005 in 1987-88, For introduction of Special Food Production Programme much larger number of tube wells may be energised in 1988-89. However target for 1988-89 has been fixed at 15160.
Government of West Bengal Development and Planning Department
Government of West Bengal Development and Planning Department